Physics of life : the physicist's road to biology. - Blomberg, Clas (Elsevier Science, 2007)
The purpose of the book is to give a survey of the physics that is relevant for biological applications, and also to discuss what kind of biology needs physics. The book gives a broad account of basic physics, relevant for the applications and various applications from properties of proteins to processes in the cell to wider themes such as the brain, the origin of life and evolution. It also considers general questions of common interest such as reductionism, determinism and randomness, where the physics view often is misunderstood. The subtle balance between order and disorder is a repeated theme appearing in many contexts. There are descriptive parts which shall be sufficient for the comprehension of general ideas, and more detailed, formalistic parts for those who want to go deeper, and see the ideas expressed in terms of mathematical formulas. - Describes how physics is needed for understanding basic principles of biology - Discusses the delicate balance between order and disorder in living systems - Explores how physics play a role high biological functions, such as learning and thinking.